Differential analysis of transcriptome of Glutamicibacter arilaitensis under different culture temperatures - Chun-guang , Xu; Li-xia , Yang; Ji-chun , Wang; Yu-jiao, Ma; Bao-li, Yu (Mongolian Journal of Agricultural Sciences, 2024)
Low-temperature adaptation is a critical physiological process in mesophilic bacteria, yet its molecular mechanisms remain unclear. To investigate how Glutamicibacter arilaitensis strain F9 adapts to cold stress, the strain was cultured at 5°C (F9_5), 10°C (F9_10), and 25°C (F9_25). High-throughput transcriptome sequencing was performed to analyze differentially expressed genes (DEGs) across these conditions. Gene expression differences were identified and subjected to Gene Ontology (GO) enrichment analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis. A total of 731 DEGs were identified between the F9_25 and F9_10 groups, 747 between F9_25 and F9_5, and 265 between F9_10 and F9_5, with 65 shared DEGs across all comparisons. GO enrichment analysis revealed that the DEGs were primarily associated with cellular energy metabolism, amino acid biosynthesis, and membrane components. KEGG pathway analysis identified 20 significantly enriched pathways, with key differences observed in: dicarboxylate metabolism, ABC transporters, and two-component systems in the F9_25 and F9_10 comparison; two-component systems, pyruvate metabolism, and glyoxylate/dicarboxylate metabolism in the F9_25 and F9_5 comparison; and fatty acid degradation, tryptophan metabolism, and two-component systems in the F9_10 and F9_5 comparison. To survive low-temperature stress, strain F9 modulated gene expression to counteract the reduction in enzyme activity and protein efficiency. This regulation helped maintain membrane fluidity, ensuring proper substance exchange and signal transduction, while also securing sufficient energy and biosynthetic precursors for essential cellular functions.